Metabarcoding and microscopy characterization of phytoplankton from frontal areas of the Argentine Sea - Almandoz, Gastón Osvaldo; Fabro, Elena; Sprong, Pim; Mascioni, Martina; Antoni, Julieta; Ferrario, Martha; Metfies, Katja; Barrera, Facundo Matias (Frontiers in Marine Science, 2024)
The Argentine Sea is worldwide recognized as a highly productive area, characterized by extensive phytoplankton blooms during spring and summer. Despite the well-known importance of frontal areas for biomass accumulation, phytoplankton diversity remains poorly studied. In an unprecedented approach for the Argentine Sea, we combined microscopy and 18Sv4 metabarcoding analyses for a refined assessment of summer phytoplankton composition in three understudied frontal areas of the Argentine Sea (≈43°−55°S), with contrasting oceanographic conditions. Metabarcoding and microscopy analyses agreed on the detection of the dominant phytoplanktonic groups in the different frontal areas studied; chlorophytes in Valdés Peninsula, dinoflagellates in waters off Blanco Cape, and diatoms in de los Estados Island. The analysis of the phytoplankton community was significantly enriched by combining both techniques, microscopy provided cell abundances and biomass data and metabarcoding provided greater detail on species composition, revealing an important specific richness of dinoflagellates, diatoms and other delicate groups, such as chlorophytes. However, we also considered differences between the methods for certain taxa at a lower taxonomic level (species/genus) of the dominant taxa, such as the underestimation of the diatoms Asterionellopsis glacialis and Pseudo-nitzschia spp. and the overestimation of Chaetoceros contortus by metabarcoding in comparison to microscopic counts. The detection of several taxa belonging to small and delicate groups, previously overlooked due to the lack of distinct morphological features, establishes a baseline for future studies on phytoplankton diversity in the Argentine Sea.